Opracowanie w chmurze czy chmury nad opracowaniem? Automatyczne indeksowanie dokumentów a biblioteki - Włodarczyk, Bartłomiej (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The paper presents recent research in the field of automatic indexing of text documents, inter alia, in libraries, and the attitudes of Polish academic librarians towards the computerization of the subject cataloging. The methods of literature review and survey were used along with the analysis of Polish academic curricula in the field of library and information science. The article demonstrates on several examples that the similarities in document layout and the topical diversity or homogeneity are the key factors in the computerization of cataloging. The survey conducted amongst Polish subject indexing specialists from academic libraries shows that they have highly limited knowledge about automatic indexing. The results are then compared with the findings of the study on German- and English-speaking librarians’ opinions about automatic subject indexing. They are similar to the outcomes of the previous research by Alice Keller into the attitudes of, among others, the English-speaking subjects.